Developmental Potential of Abnormally Fertilized Oocytes and the Associated Clinical Outcomes - Chen, Xiao; Shi, Shuai; Mao, Jiating; Zou, Libo; Yu, Keda (Frontiers in Physiology, 2020)
This study aims to investigate the embryo development potential of extending culture of abnormally fertilized zygotes with no pronuclear (0PN) and monopronuclear (1PN) and poor-quality day 3 embryos and to determine the associated clinical outcomes. This is a retrospective study performed between January 2014 and May 2018 at Jinhua People’s Hospital. The normal developed embryos and the abnormal 0PN, 1PN and poor-quality day 3 embryos were cultured to day 5 or 6 for embryo transfer. Clinical outcomes resulting from abnormal embryos and normal developed embryos were compared. A total of 6466 embryos (1542 0PN, 852 1PN and 4072 poor-quality day 3 embryos) from 831 treatment cycles were cultured to the blastocyst stage. The total blastulation rate was 17.3% (1121/6466) with 18.2% in 0PN, 26.1% in 1PN and 15.2% in poor-quality day 3 embryos. The rate for good-quality blastocyst formation was 9.5% (616/6466) with 11.2% in 0PN group, 14.8% in 1PN group and 7.8% in poor-quality day 3 embryos, respectively. Blastulation rates of 0PN and 1PN derived from intracytoplasmic sperm injection (ICSI) were significantly lower compared with in vitro fertilization group. A total of 243 cycles were transferred with blastocysts originating from abnormal embryos, resulting in 109 (44.9%) clinical pregnancies and 19 (17.4%) miscarriages; in the control group, a total of 350 cycles result in 214 (61.1%) clinical pregnancies and 18 (8.4%) miscarriages. The live birth rate was significantly lower in abnormal embryo group than that in control group. Collectively, conventional in vitro fertilization derived 0PN and 1PN zygotes, not ICSI, together with day 3 embryos with poor quality were able to reach blastocyst stage and produce a fair pregnancy rate and live birth rate.